9.0k views
20 votes
Solve please. Correctly
3(1 - 2a) = -3a - 18

User Henhuy
by
4.7k points

1 Answer

9 votes

Answer:

a = 7

Explanation:

3(1 - 2a) = -3a - 18

3 - 6a = - 3a - 18

Add 18 to each side:

3 + 18 - 6a = - 3a - 18 + 18

21 - 6a = - 3a

Add 6a to each side:

21 - 6a + 6a = - 3a + 6a

21 = 3a

3a = 21

Divide each side by 3:

3a ÷ 3 = 21 ÷ 3

a = 7

User Xeperis
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.